Interventions to Improve Quality of Life and Knowledge in Hypersensitivity PneumonitisTake-home Points - Kerri I. Aronson, MD; Nancy Holbrook, MD; Armani Edgar, BS; Michaela R. Anderson, MD; Jamuna K. Krishnan, MD; Robert J. Kaner, MD; Anna J. Podolanczuk, MD; Fernando J. Martinez, MD; Jonathan N. Tobin, PhD; Monika M. Safford, MD (CHEST Pulmonary)
Background: Behavioral and educational interventions are promising approaches to improve health-related quality of life (HRQOL); however, few have been studied in hypersensitivity pneumonitis (HP) or other interstitial lung diseases (ILDs). The objective of this study was to gather ILD clinicians’ current practices and perspectives on the management of HRQOL and disease-specific education in HP, level of knowledge about, and attitudes toward behavioral and educational interventions and to identify potential clinician-perceived barriers to address during intervention development. Study Question: What are the current practices and perspectives of ILD clinicians regarding the management of HRQOL and disease-specific education, and what is their level of knowledge about and attitude toward a potential virtual behavioral and educational intervention to address HRQOL in HP? Study Design and Methods: An electronic survey was administered to ILD clinicians across the United States. Survey data were analyzed using descriptive statistics, and open-ended questions were analyzed using qualitative content analysis. Results: Seventy-four clinicians responded to the survey, of whom 93% identified as physicians. All respondents (100%) indicated that offering an intervention to improve HRQOL in their patients with HP is either very important or absolutely essential. Only 5% of clinicians reported currently using a validated assessment tool to measure HRQOL. When asked about specific behavioral intervention techniques, most clinicians (92%) reported possessing a small amount of or zero knowledge about peer coaching interventions and a small amount of or zero knowledge (69%) about cognitive behavioral therapy principles. Despite this, most clinicians (68%) desire the ability to educate their patients about these potentially effective behavioral interventions, and most clinicians (67%) indicated the desire to reinforce the principles of an intervention after completion. Perceived barriers to referring patients to a virtually delivered behavioral intervention included time constraints, availability and access for all patients, cost and reimbursement, and difficulty with technology. Interpretation: Clinicians in this survey unanimously agree that interventions to improve HRQOL and knowledge are needed for people living with HP. Clinicians’ desire for involvement in education, referral, and reinforcement of these interventions will require clinician education in behavioral strategies and implementation-related strategies early in the development process.